Ribā dan Ketidakadilan Sistem Ekonomi Kapitalisme, Sebuah Kajian Teoritis - Muhammad Ghozali; Yusi Septa Prasetya (University of Darussalam Gontor, 2017)
The failures of capitalism economic in realizing justice and prosperity is due to the implementation of the interest system (usury system). In the long term usury system pose a huge gap between communities. Giving a variety of impacts on the economy of ummah. As the imbalance of the real sector and monetary sector, poverty and others. People, their life has been shackled by the economic system that allow the practice of interest or on the practice of usury is certainly contrary to the society ideals which is social justice, contrary to a life filled with love In fact, not a few countries receiving assistance of these loans were destroyed due to the large amount of foreign debt. Islamic economic as economy system resurfaced again trying to bring about justice and the welfare of his followers to abolish interest (riba) and replace with a system of profit sharing (profit loss sharing). As one of alternative to achieve economic justice. The underlying revenue sharing system embodiment of justice in various financial sector and the real sector. As for the elimination of usury system that forcenturies held in various countries. To errasing the practice of usury rate system, Islamic economics has its own rules in eliminating usury system and replace it with a system of profit sharing (profit loss sharing) to achieve justice in economic life and charity as a form of wealth distribution. Profit loss sharing system with the end result-oriented on businesses without unknowning the share out either be positive or negative. Each parties will share in the same way